Il primo dimostratore Smart City applicato ai Beni Culturali - Papi, Luca (Archeomatica, 2014)
Smart City living lab on the Island of Ortigia in Siracusa - UNESCO World Heritage site since 2005 - is focused on the valorization of the historical heritage present on that territory, in order to facilitate the management and promotion of intelligent, creating direct communication channels, providing personalized information and services in real time for tourists and citizens. The implemented solutions represent a national preview of the project and allow an immersive experience of archaeological heritage through the use of Web 2.0 technologies and intuitive navigation consistent with all contents across all media available to users.